Production of kokum juice powder using spray drying technology - ALFONSA JAMES; Amrutha K; Dr. Sudheer K. P (Guide) (Tavanur 2016 Department of Food and Agricultural Process Engineering)
Production of kokum juice powder using spray drying technology
Production of kokum juice powder using spray drying technology